2012
DOI: 10.7763/ijbbb.2012.v2.67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Fermentation Substrates and Growth Temperature on Exopolysaccharide Production by Streptococcus Thermophilus BN1

Abstract: Abstract-The purpose of this research was to evaluate, the effect of incubation temperature and some substrates on exopolysaccharides (EPS) production. The S. thermophilus BN1 an EPS-producer strain isolated from cow milk was examined in this study. Skimmed milk, whole milk and cheese whey, were selected as culture media and two different temperatures were also tested. The EPS produced in the different studied conditions was purified and quantified. The strain BN1 was able to produce EPS in all established con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Each strain has its own optimal temperature for cell development and EPS production. S. thermophiles BN1 synthesized EPS highest at temperature of 37 °C [16]. However, in the study of L. De Vuysta et al [17], the optimal temperature for EPS production of S. thermophiles was at 42 °C.…”
Section: Effect Of Incubation Temperature On Eps Production Of L Plamentioning
confidence: 90%
“…Each strain has its own optimal temperature for cell development and EPS production. S. thermophiles BN1 synthesized EPS highest at temperature of 37 °C [16]. However, in the study of L. De Vuysta et al [17], the optimal temperature for EPS production of S. thermophiles was at 42 °C.…”
Section: Effect Of Incubation Temperature On Eps Production Of L Plamentioning
confidence: 90%
“…EPS production is determined by the growth stage of bacteria, composition of culture medium (type of carbon and nitrogen sources, and presence of other nutrients), temperature, and pH, and/or by the presence of adjuvant microflora [2,3,62,72,82,86,92,93] (Tab. I).…”
Section: Factors Affecting Exopolysaccharides Synthesis By Lactic Acimentioning
confidence: 99%
“…Ample studies have addressed the effect of culture medium composition on the concentration of EPS produced by LAB [69,72,82,86,92]. The Lb.…”
Section: Factors Affecting Exopolysaccharides Synthesis By Lactic Acimentioning
confidence: 99%
“…One study by Pawar., et al [25] reported the maximum EPS production of 5 gm/l by one isolate predicted as Alpha Proteobacterium group, obtained from saline soil, suggesting that different ecological environment may possess different diversity of such EPS-producing bacteria and their EPS producing capability may differ according to the type of bacteria and even the strains. In addition, the EPS production largely depends on the substrate composition and environmental conditions [26].…”
Section: Phenotypic and Biochemical Characterization Of The Epsproducmentioning
confidence: 99%